Confirmation of Xp22.11 Duplication as a Germline Susceptibility Alteration in a Wilms Tumor Arising in Horseshoe Kidney. (4th July 2022) - Zhou, Hui-fang; Amarillo, Ina E.; Snyder, Stacy; Granadillo, Jorge L.; O'Conor, Christopher J.; Dillon, Patrick; Wilson, David; Huang, Frederick S.; Dehner, Louis P.; He, Mai
Abstract: Background There is strong evidence of a genetic contribution to Wilms tumor, such as WT1 gene variation or epigenetic changes at chromosome locus 11p15. A previous genome wide association study (GWAS) of Wilms tumor identified other significant association loci including Xp22. Case report: A 4-year-old girl developed a Wilms tumor of the left isthmus of a horseshoe kidney. Chromosomal microarray analysis (CMA) of peripheral blood showed a 563 kb copy number gain at Xp22.11 that included PRDX4 and ZFX . PRDX4 has been shown to play an active role in the tumorigenesis of malignant neoplasms in various organs. Beckwith-Wiedemann methylation analysis and WT1 sequencing were negative. Whole exome sequencing of peripheral blood revealed pathogenic variant in PMS2 gene (c.765C > A), which is consistent with Lynch syndrome. Conclusion: We report a case of Wilms tumor with germline Xp22.11 duplication which further supports this locus as germline susceptibility alteration for Wilms Tumor.